British Association of Dermatologists guidelines for the management of people with vitiligo 2021. (1st January 2022) - Eleftheriadou, V.; Atkar, R.; Batchelor, J.; McDonald, B.; Novakovic, L.; Patel, J.V.; Ravenscroft, J.; Rush, E.; Shah, D.; Shah, R.; Shaw, L.; Thompson, A.R.; et al.
Abstract: Linked Comment: K. Ezzedine and A.G. Pandya. Br J Dermatol 2022; 186:3–4 . Plain language summary available online